The Usborne book of famous lives - Reid, Struan; Reid, Struan; Watton, Ross (Tulsa, OK : EDC, 1997)
Profiles the lives of key individuals in history who have helped to shape the modern world.
Inventors -- Scientists -- Explorers -- Kings & queens -- Famous women.
Includes bibliographical references and index.
9-12.
4-8.
Keywords: Inventors -- Biography; Scientists -- Biography; Explorers -- Biography; Kings and rulers -- Biography; Women -- Biography